Oviposition preference of Zeugodacus cucurbitae (Diptera: Tephritidae) on melon manis terengganu, Cucumis melo var. inodorus - Saidi, Nur Syahida Wajdah; Mohamed, Salmah; Azeli, Nor Aminah Azizol; Yusof, Nur Athiqah Md; Ngah, Norhayati; Adam, Nur Azura (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Understanding the ovipositional preferences of insect pests is essential for developing effective management strategies in agricultural systems. Zeugodacus cucurbitae (Coquillett) is a highly destructive tephritid fruit fly that infests fruits at various maturity stages, causing significant damage to economically important crops such as Melon Manis Terengganu (MMT). This study investigated the ovipositional preference of Z. cucurbitae across three fruit maturity stages—unripe, ripe, and fully ripe—under no-choice and choice experimental conditions. In the no-choice experiment, pupal formation (7.44 ± 2.10 pupae) and adult emergence (6.20 ± 2.03 flies) were significantly lower (P < 0.05) in unripe MMT, whereas the percentage of adult emergence and sex ratio did not differ significantly (P > 0.05) among fruit maturity stages. Under choice conditions, pupal formation was also significantly lower (P < 0.05) in unripe MMT (11.40 ± 4.68 pupae), while fully ripe fruits supported significantly higher (P < 0.05) male (51.70 ± 21.07%) and female (55.00 ± 26.59%) emergence. Correlation analysis revealed significant relationships (P < 0.05) between pupal formation, adult emergence, and fruit characteristics in the choice experiment. These findings demonstrate a strong preference of Z. cucurbitae for fully ripe MMT as oviposition sites, indicating that fruit maturity plays a critical role in host selection. This study provides valuable insights for the development of targeted pest management strategies, including early-stage fruit protection, to reduce infestation in MMT cultivation.